Renin-angiotensin and kallikrein-kinin systems in diabetic retinopathy - Igić, Rajko (Scripta Medica, 2019)
This brief review describes how two complex systems, the renin-angiotensin system (RAS) and the kallikrein-kinin system (KKS), affect the retina. It emphasizes the important physiological actions of components of these systems, the protective effectiveness of angiotensin I converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARB) in diabetic retinopathy, and suggests as well the therapeutic possibilities for treatment of diabetic retinopathy by selective activation of bradykinin receptors (B1 and B2). The preferred pharmacological target likely would be activation of B1 or B2 receptors.